Effect of Nigella sativa oil extract on inflammatory cytokine response and oxidative stress among people with type 2 diabetes mellitus: a randomized, double-blind, placebo controlled trial - Hadi, Saeid; Mirmiran, Parvin; Daryabeygi-Khotbesara, Reza; Hadi, Vahid (Progress in Nutrition, 2018)
Objectives: Diabetes mellitus (DM) is the most common chronic disease and a challenging global health problem. Inflammation plays a key role in the pathogenesis of DM. The experimental studies have shown that Nigella sativa (N. sativa) oil extract is a potential anti-inflammatory and anti-oxidant substance. The present study was conducted to evaluate the anti-inflammatory and antioxidant effects of N. sativa among adults diagnosed with type 2 diabetes (T2D). Methods: A double-blind placebo controlled trial was designed. A total of 43 participants were assigned into either intervention (N=23) or control (N=20) conditions. The intervention group received 500 mg N. sativa capsules twice a day, while control group received identical amounts of placebo capsules twice a day for 8 weeks. Dietary intake, physical activity, anthropometric indices, and fasting blood samples were measured at baseline and one week post-intervention. Results: Findings revealed significant reductions in malondialdehyde (MDA) and nitric oxide (NO) within the intervention condition, although between-group analysis did not show any significant changes neither for MAD nor NO. Besides, within- and between-group analyses did not show any significant differences pre- and post-intervention for interleukin 1β (IL-1β), tumor necrosis factor-α (TNF-α), superoxide dismutase (SOD), and catalase (CAT). Conclusions: The current study revealed favorable effects for N. sativa oil extract in reducing MDA and NO among people with T2D. However, future research is needed to establish potential anti-inflammatory and anti-oxidative responses of N. sativa in diabetes.